2002
DOI: 10.1046/j.0022-7722.2002.00001.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent left hepatic venous connection with the right atrium and the ductus venosus

Abstract: An anomalous left hepatic vein opening independently of the coronary sinus into the right atrium was found in the cadaver of an 88-year-old Japanese man. This vein originated from the left lobe of the liver, perforated the diaphragm at the left side of the vena caval foramen and opened into the right atrium. The left hepatic vein anastomosed mutually with the middle hepatic vein at the level of venule. The ligamentum venosum originated from the left branch of the portal vein and was connected directly to the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 9 publications
0
19
0
1
Order By: Relevance
“…2,5,6,10 The occurrence of left hepatic vein drainage into the right atrium may be explained due to the persistence of the left vitelline connection with the left sinus horn, 14,15 as was the case in our patient. This is an extremely rare finding that has been reported only once in association with PLSVC 16 and in another report as an isolated autopsy finding. 15 …”
Section: Embryologymentioning
confidence: 88%
“…2,5,6,10 The occurrence of left hepatic vein drainage into the right atrium may be explained due to the persistence of the left vitelline connection with the left sinus horn, 14,15 as was the case in our patient. This is an extremely rare finding that has been reported only once in association with PLSVC 16 and in another report as an isolated autopsy finding. 15 …”
Section: Embryologymentioning
confidence: 88%
“…Previous studies reported that the accessory foramina of the VHs on the diaphragm could be on either side of the CO. 3,7,8 In the present study, we found them on the right side of the CO in all Type 1 cases (posterior to, at the same level with and anterior to the CO in 6, 2 and 1 case, respectively). One of the FVH in Types 2 and 3…”
Section: Variations Of Hepatic Veins Opening Into the Inferior Vena Cavamentioning
confidence: 67%
“…In general, three main hepatic veins drain the liver into the inferior vena cava below the diaphragm, 12 and a single hepatic vein draining directly to the right atrium is occasionally reported. 13,14 However, it is rare to see the three main hepatic veins draining directly to the right atrium. A search of PubMed using the keywords, right atrium and hepatic vein, did not find any reports of this anomaly.…”
Section: Discussionmentioning
confidence: 98%